2018
DOI: 10.1200/jgo.17.00144
|View full text |Cite
|
Sign up to set email alerts
|

Desire for Information and Preference for Participation in Treatment Decisions in Patients With Cancer Presenting to the Department of General Surgery in a Tertiary Care Hospital in India

Abstract: PurposeProviding appropriate information to patients about their illness helps them to cope with the diagnosis. Shared decision making is a key concept in managing patients with cancer. There are no data available about the desire for information and preference for participation in treatment decisions among Indian patients with cancer. The objective of this study was to estimate the proportion of patients who have information needs and to study the patient preference for participation in treatment decisions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…Gilani et al and Kraetschmer et al in their studies found that patients and accompanying attendants prefer an active role when the trust levels are less with the treating surgeons [12][13]. Sankar et al found that Indian patients and their accompanying attendants are used to a paternalistic approach when the trust levels are higher with their treating surgeon [7]. This may be the reason why the majority of this study's patients played a passive role in MMT.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Gilani et al and Kraetschmer et al in their studies found that patients and accompanying attendants prefer an active role when the trust levels are less with the treating surgeons [12][13]. Sankar et al found that Indian patients and their accompanying attendants are used to a paternalistic approach when the trust levels are higher with their treating surgeon [7]. This may be the reason why the majority of this study's patients played a passive role in MMT.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, similar results were seen with regards to the preference for the active role while there was an abrupt contrast in the number of patients preferring a collaborative or passive role. The majority of Indian patients prefer a passive role in their treatment due to a lower level of education and their preference to give importance to their health than their personal appearance [7,11]. Gilani et al and Kraetschmer et al in their studies found that patients and accompanying attendants prefer an active role when the trust levels are less with the treating surgeons [12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with cancer need to be aware of their potential treatment options at all stages of their illness trajectory. Based on the findings in previous studies, patients may face challenges in making personal decisions about treatment during a highly stressful time (29). However, time is an important factor in cancer treatment, given the potential for disease advancement.…”
Section: Discussionmentioning
confidence: 99%